An examination of the molecular control of feed efficiency in beef cattle - MCKENNA, CLARE (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2018)
Global agriculture is faced with the enormous challenge of feeding a rapidly growing population while being cognizant of the environmental footprint of such endeavours. A consequence of increased meat consumption worldwide is an increase in demand for animal feed. As feed provision is the single largest cost incurred by beef farmers, cattle with improved feed efficiency are central to profitable, sustainable and efficient beef production. A major constraint to genetic progress in feed efficiency is the difficulty and enormous expense of measuring it directly. Therefore, robust cost-effective molecular-based biomarkers for feed efficiency are necessary. This multidisciplinary thesis aimed to: (i) establish and physiologically characterise two populations of cattle, genetically and phenotypically divergent for feed efficiency as measured by residual feed intake (RFI); (ii) examine the premise that efficiency of energy transduction in cattle is a function of mitochondrial abundance and mitochondrial functional efficiency; (iii) examine the expression of genes involved in fatty acid metabolism in adipose tissue from animals divergent for RFI; and (iv) to examine the effect of RFI status, gender and diet as well as their interactions on targeted and global transcriptomic expression across three metabolically important tissues. The observations from this work suggest that firstly variation in mitochondrial number and/or enzymatic capacity may not be major contributors to variation in RFI. Secondly, the expression of GLUT4 in adipose tissue is related to RFI and has potential to be investigated as a biomarker for RFI in cattle. Thirdly, transcriptomic analysis in liver tissue from bulls divergent for RFI, revealed evidence that efficient heifers had an enhanced capacity for mitochondrial function in muscle tissue, while oxidative response, protein mediation and cell signaling are likely to be processes that are influencing variation in feed efficiency in bull liver tissue. Finally, effects of RFI on gene expression in muscle of beef cattle are not consistent across breed type or dietary phase. In conclusion, while the results of this thesis provide a greater insight into the biological mechanisms governing RFI in cattle, they challenge the practicality of developing a robust set of biomarkers for RFI that would be of ubiquitous utility to the beef cattle industry.
APPROVED
Keywords: feed efficiency; cattle; transcriptomics; mitochondria